TINGKAT PENGETAHUAN ORANG TUA TENTANG COVID-19 DI RUANG RAWAT INAP PEDIATRIK RUMAH SAKIT ADVENT BANDUNG - Nani Simbolon (Klabat Journal of Nursing, 2021)
ABSTRACT Coronavirus Disease (COVID-19) is a pandemic disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and World Health Organization shows the increase number of confirmed cases from various countries massively. It is hoped that through good understanding and knowledge about COVID-19 from all elements of society it can form a behavior in accordance with the protocol and it can break the chain of transmission of the COVID-19 virus. This study aims to describe the level of knowledge about COVID-19 in pediatric’s parents at Bandung Adventist Hospital. This research design is descriptive quantitative, and the sample taken through purposive sampling with 50 people. The instrument used was a knowledge questionnaire about Covid-19. The result of this research found that the level of parents knowledge about COVID-19 is in the good category (84%). Keywords: Knowledge, Coronavirus Disease ABSTRAK Coronavirus Disease 2019 (COVID-19) merupakan penyakit pandemi yang disebabkan oleh virus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) dan data organisasi kesehatan dunia menunjukkan peningkatan jumlah kasus terkonfimasi dari berbagai negara secara masif. Diharapkan melalui pemahaman dan pengetahuan yang baik tentang COVID-19 dari seluruh elemen masyarakat dapat membentuk perilaku yang sesuai dengan protokol sehingga dapat memutuskan mata rantai penularan virus COVID-19. Penelitian ini bertujuan untuk melihat gambaran tingkat pengetahuan orang tua pasien pediatrik yang dirawat di Rumah Sakit Advent Bandung. Desain penelitian ini adalah kuantitatif deskriptif, dan jumlah sampel yang diambil menggunakan teknik total sampling adalah sebanyak 50 orang. Instrumen yang digunakan adalah kuesioner pengetahuan tentang Covid-19. Hasil penelitian ini memperoleh gambaran tingkat pengetahuan orang tua tentang COVID-19 berada dalam kategori yang baik (84%).